2020
DOI: 10.1038/s41380-020-00960-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetically encoded sensors enable micro- and nano-scopic decoding of transmission in healthy and diseased brains

Abstract: Neural communication orchestrates a variety of behaviors, yet despite impressive effort, delineating transmission properties of neuromodulatory communication remains a daunting task due to limitations of available monitoring tools. Recently developed genetically encoded neurotransmitter sensors, when combined with superresolution and deconvolution microscopic techniques, enable the first micro- and nano-scopic visualization of neuromodulatory transmission. Here we introduce this image analysis method by presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 120 publications
2
12
0
Order By: Relevance
“…The finding of restricted neuromodulatory transmission has multiple implications. Like several other transmission parameters, such as the amount of released transmitter, width of synaptic clefts, and location of postsynaptic transmitter receptors across various synapses (Savtchenko and Rusakov, 2007;Savtchenko et al, 2013;Haas et al, 2018), spatial spread length constants of neurotransmitters (i.e., glutamate, ACh, monoamines, and neuropeptides) are almost identical across various cell types (Lin et al, 2021;Zhu et al, 2020). These results support the idea that synapses optimize their nanoscale presynaptic and postsynaptic organizational elements to maximize efficacy and precision.…”
Section: Biological Applicationssupporting
confidence: 68%
See 3 more Smart Citations
“…The finding of restricted neuromodulatory transmission has multiple implications. Like several other transmission parameters, such as the amount of released transmitter, width of synaptic clefts, and location of postsynaptic transmitter receptors across various synapses (Savtchenko and Rusakov, 2007;Savtchenko et al, 2013;Haas et al, 2018), spatial spread length constants of neurotransmitters (i.e., glutamate, ACh, monoamines, and neuropeptides) are almost identical across various cell types (Lin et al, 2021;Zhu et al, 2020). These results support the idea that synapses optimize their nanoscale presynaptic and postsynaptic organizational elements to maximize efficacy and precision.…”
Section: Biological Applicationssupporting
confidence: 68%
“…Indeed, initial experimental work validates that genetically encoded sensors, when combined with superresolution and deconvolution microscopic analysis, can decode the fundamental synaptic properties of neuromodulatory transmission (Borden et al, 2020;Lin et al, 2021;Zhu et al, 2020). It is important to note that both high-performing sensors and good practical solutions are critical for the success of biological applications (Lin et al, 2021;Zhu et al, 2020). We discussed how genetically encoded neuromodulatory transmitter sensors might advance our understanding of Alzheimer's disease, sleep-wake cycle and related sleep disorders, and tumorigenesis.…”
Section: And Permitmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently developed genetically encoded sensors for neuromodulatory transmitters provide new opportunities to monitor and quantitate neuromodulation (Sabatini and Tian, 2020; Labouesse and Patriarchi, 2021; Lin et al, 2021; Wu et al, 2022). Indeed, both theoretical (Lin et al, 2021) and preliminary experimental (Zhu et al, 2020) analyses have shown that several genetically encoded transmitter sensors emit a large number of photons following transmitter binding to enable high-resolution visualization of the process. However, most genetically encoded transmitter sensors remain underused, due mainly to the lack of user-friendly analysis programs for high-sensitivity, high-resolution visualization of transmitter release.…”
Section: Introductionmentioning
confidence: 99%